New Developments in Goal Setting and Task Performance. - Locke, Edwin A. (Taylor and Francis, 2012)
This book concentrates on the last twenty years of research in the area of goal setting and performance at work. The editors and contributors believe goals affect action, and this volume will have a lineup of international contributors who look at the recent theories and implications in this area for IO psychologists and human resource management academics and graduate students.